2020
DOI: 10.1136/bmjopen-2019-035345
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study evaluating management of burns in the community in clinical practice in the UK: costs and outcomes

Abstract: ObjectiveTo evaluate health outcomes, resource use and corresponding costs attributable to managing burns in clinical practice, from initial presentation, among a cohort of adults in the UK.DesignRetrospective cohort analysis of the records of a randomly selected cohort of 260 patients from The Health Improvement Network (THIN) database who had 294 evaluable burns.SettingPrimary and secondary care sectors in the UK.Primary and secondary outcome measuresPatients’ characteristics, wound-related health outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…A systematic review showed that the mean cost per patient with burn in high-income countries was US$ 88,218 ( 17 ). In particular, the average cost of per patient burn care has been reported as US$ 6,755 in Japan ( 20 ), US$ 15,250 in Turkey ( 21 ), US$ 73,532 in Australia ( 22 ), US$22,759 (€26,540) in the Netherlands ( 23 ), US$ 114,576 (€105,116) in the United Kingdom (UK; for a patient with 27% TBSA) ( 7 ), US$ 22,617 in the United Kingdom per burn care in primary and secondary care settings ( 24 ), US$ 2,283 in Nepal as direct cost for inpatient burn treatment ( 25 ), US$ 1,060.5 in North India, US$ 704 in Bangladesh, and US$ 559.85 per patient in Malawi ( 25 ). Data were different in high vs. low- and middle-income countries (LMICs; mean costs per patient $88,218 vs. $5,196), as in the last countries there are different healthcare and finance structures, price levels, treatment protocols, and therapeutic possibilities, and limited resources ( 17 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that the mean cost per patient with burn in high-income countries was US$ 88,218 ( 17 ). In particular, the average cost of per patient burn care has been reported as US$ 6,755 in Japan ( 20 ), US$ 15,250 in Turkey ( 21 ), US$ 73,532 in Australia ( 22 ), US$22,759 (€26,540) in the Netherlands ( 23 ), US$ 114,576 (€105,116) in the United Kingdom (UK; for a patient with 27% TBSA) ( 7 ), US$ 22,617 in the United Kingdom per burn care in primary and secondary care settings ( 24 ), US$ 2,283 in Nepal as direct cost for inpatient burn treatment ( 25 ), US$ 1,060.5 in North India, US$ 704 in Bangladesh, and US$ 559.85 per patient in Malawi ( 25 ). Data were different in high vs. low- and middle-income countries (LMICs; mean costs per patient $88,218 vs. $5,196), as in the last countries there are different healthcare and finance structures, price levels, treatment protocols, and therapeutic possibilities, and limited resources ( 17 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the increased risk of infection and deceleration in wound healing are among the main concerns for caring for burns patients, a broad range of topical medicines that contain antiseptics and antibiotics nowadays are prescribed for treating burns 4,5 . Among these medications, 1% silver sulfadiazine (SSD) as a topical medicine is commonly prescribed to treat and prevent second‐degree burns from being infected 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the increased risk of infection and deceleration in wound healing are among the main concerns for caring for burns patients, a broad range of topical medicines that contain antiseptics and antibiotics nowadays are prescribed for treating burns. 4,5 Among these medications, 1% silver sulfadiazine (SSD) as a topical medicine is commonly prescribed to treat and prevent second-degree burns from being infected. 6 When mixed with body fluids, however, SSD creates a thick pseudo-eschar that is difficult and painful to remove, 7 and due to its stickiness to the wound and its noxious effects on restoring keratinocytes, SSD can delay the wound healing process and leaves a puckered scar.…”
mentioning
confidence: 99%
“…Approximately 3.8 million people with a wound were treated by the National Health Service (NHS, United Kingdom) in 2017/2018 with an annual cost of £8.3 billion [ 13 ]. For example, the average cost of treating a burn over a 24-month period is approximately £17,000 in the NHS [ 14 ].…”
Section: Introductionmentioning
confidence: 99%